Age-period-cohort analysis of lung cancer mortality inequalities in Southern Spain: missed opportunities for implementing equitable tobacco control policies - Juan Antonio Córdoba-Doña; Encarnación Benítez-Rodríguez; Antonio Escolar-Pujolar; Vanessa Santos-Sánchez (BMC, 2023)
Abstract Background Lung cancer mortality in European countries shows different epidemiological patterns according to sex and socioeconomic variables. Some countries show decreasing rates in both sexes, while others show a delayed profile, with increasing mortality in women, inconsistently influenced by socioeconomic status. Our aim was to evaluate the effect of age, period and birth cohort on lung cancer mortality inequalities in men and women in Andalusia, the southernmost region in Spain. Methods We used the Longitudinal Database of the Andalusian Population, which collects demographic and mortality data from the 2001 census cohort of more than 7.35 million Andalusians, followed up between 2002 and 2016. Mortality rates were calculated for men and women by educational level, and small-area deprivation. Poisson models were used to assess trends in socioeconomic inequalities in men and women. Finally, age-period-cohort (APC) models were used separately for each educational level and gender. Results There were 39,408 lung cancer deaths in men and 5,511 in women, yielding crude mortality rates of 78.1 and 11.4 × 105 person-years, respectively. In men higher mortality was found in less educated groups and inequalities increased during the study period: i.e. the rate ratio for primary studies compared to university studies increased from 1.30 (CI95:1.18-1.44) to 1.57 (CI95:1.43-1.73). For women, educational inequalities in favour of the less educated tended to decrease moderately. In APC analysis, a decreasing period effect in men and an increasing one in women were observed. Cohort effect differed significantly by educational level. In men, the lower the educational level, the earlier the peak effect was reached, with a 25-year difference between the least-educated and college-educated. Conversely, college-educated women reached the peak effect with a 12-year earlier cohort than the least-educated women. The decline of mortality followed the same pattern both in men and women, with the best-educated groups experiencing declining rates with earlier birth cohorts. Conclusions Our study reveals that APC analysis by education helps to uncover changes in trends occurring in different socioeconomic and gender groups, which, combined with data on smoking prevalence, provide important clues for action. Despite its limitations, this approach to the study of lung cancer inequalities allows for the assessment of gaps in historical and current tobacco policies and the identification of population groups that need to be prioritised for public health interventions.